(3Gdbje GdJi JYcSgG GdCadGe GdQhGFjI GdeUQjI ai GdaJQI eGHjf (B2005: 2015 (3h JCKjQgG Ydi GdCWaGd(B: s (3OQGSI eSMjI (B/ s - (3Ced ESeGYjd YHOGdQGRb eMehO eQRhbs; (3fSeI CMeO jhfS GdHWQjb (B: s ((3GdbGgQI (B: s (3Ced ESeGYjd YHOGdQGRb eMehO eQRhb (B: s, 2017)
(3gPg GdOQGSI JfJei dHMhK bjGS JCKjQGJ hSGFd GdEYdGe ShGA GdShSjhdhLjI Ch GdSjchdhLjI h GSJgOaJ gPg GdOQGSI GdCWaGd JMOjkOG ef Sf GdJGSYI h MJi GdKGfjI YTQI HgOa GdJYQa Ydi GdJCKjQGJ GdfGLeI Yf JYQV gDdGA ddCadGe GdQhGFjI GdeUQjI(B: (3deYQaI EPG eG cGf gfGc JCKQ HTcd Ch HBNQ HgPg GdeVGejf GdajdejI(B: (3h EPG cGf gfGc eLGd dJCKQ GdCWaGd HJdc GdeVGejf aeG gj CTcGd Pdc GdJCKQ h fWGbGJ MOhKg(B. (3ceG SYJ GdOQGSI deYQaI CHQR CfeGW GdhSGWI GdhGdOjI h GdGSJQGJjLjGJ GdJi jeGQSgG ChdjGA CehQ GdCWaGd YjfI GdOQGSI GdejOGfjI ddMO ef GdJYQV dJdc GdeVGejf GdajdejI(B: (3h cPdc dJbdjd GdCNWGQ GdfGLeI Yf GdJCKQ HgG(B. (3h fGbTJ GdOQGSI cd eG SHb ai EWGQ fXQjJi (B((3GdJYde GdGLJeGYi(B) (3h (B((3GdZQS GdKbGai(B) (3h Pdc HGSJNOGe efgL GdeSM(B: (3h HGdGSJYGfI HGdCOhGJ GdefgLjI GdJGdjI(B: (3GdGSJHjGf HGdebGHdI GdeHGTQI dcd ef GdCWaGd (B(12:9) (3YGkeG(B: (3h ChdjGA CehQge(B. (3ESJeGQI JMdjd eVehf d` (B55 (3ajdkeG Je EfJGLgG h YQVgG ai GdaJQI eG Hjf (B2005 (3h MJi GdYGe (B2015. (3h CLQjJ GdOQGSI GdejOGfjI Ydi (B300 (3eaQOI HhGbY (B150 (3WakdG(B: (3h(B150 (3ef ChdjGA CehQge h bO bSeJ HGdJSGhi Hjf GdeOGQS GdMchejI h GdNGUI h GdCLfHjI(B: (3ceG CLQjJ GdOQGSI GdJMdjdjI Ydi NeS h NeSjf (B(55) (3ajdkeG ef CadGe GdSjfeG GdeUQjI HhGbY (B110 (3SGYI eTGgOI JbQjkHGs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdEYdGe (B- (3bSe GdEPGYI h GdJdjaRjhfs
(3UOQ GjVG cbQU eOeLs
Keywords: (3Gdbjes; (3JCKjQ JYQV GdCWaGds; (3Yde GdEYdGe GdSjchdhLis